E-ticketing pothole road system - Poh, Xiou Hui (2023)
This project intricates on the chosen research which is E-ticketing Pothole Road System. It is an application that helps users on report potholes in a systematic way where user can upload their photos, receive notifications updated about the status of the report they made. The target audience is for road users so that they can be aware of the road conditions and make a report whenever they are on the road or in anywhere else. The problem faced by road users is there is lack of effective communication between the road users and authorities. Road users cannot receive feedback when they make a report. Road authorities cannot store and manage users’ report history in an organized way. The proposed system for this project is an android application system because it is the best fit for this project due to the process of retrieving users’ location and photos from gallery and snap photo function. Method used in this project is a computer to develop and design for the application. Compare between the existing systems and enhance it, then implement on the proposed system.